Pengaruh Hoax Terkait COVID-19 Terhadap Tingkat Kecemasan Pada Masyarakat Di Desa Babakan Karet Cianjur : The Influence of Hoaxes Related to COVID-19 on the Level of Anxiety in the Community in Babakan Karet Village, Cianjur - Maulana, Moch. Perta (Dohara POAJ, 2024)
Introduction: Corona Virus Disease or Severe Acute Respiratory Syndrome Corona Virus 2 (SARSCoV2) is an infectious disease caused by a new Corona Virus with common symptoms such as fever, weakness, cough, diarrhea and has claimed thousands of lives. Hoax is fake news that is used to spread untrue information about many things and corner a certain party. Anxiety is a reaction to a threatening situation and results in fear and discomfort. A lot of hoax information that is spread about COVID-19 causes public anxiety to increase. Methods: This research is quantitative with a pre-experimental research design. Respondents in this study amounted to 94 people. The results of the analysis were found using the Zung Self-Rating Anxiety Scale (ZSAS) questionnaire. Results: The results of the Wilcoxon test in table 4 can be concluded that the data in this study has an influence. Based on the results of the data processing, the p-value on aym-sig obtained the results of 0,000; which is < 0,05; which means that there is an influence on this study. Before being given treatment the average level of public anxiety was 32,18 (not anxious) and after treatment the result was 55,88 (mild anxiety) which was not anxious < 45 and mild anxiety was 45-59. Discussion: This study aims to analyze the effect of hoaxes related to COVID-19 on the level of anxiety in the community in Babakan Karet Village, Cianjur.